Income Analysis and Cost of Orange Grove Farming Business (Case Study in TanjungBeringin Village of Sumbul District of Dairi Regency) - Masta Sembiring (Journal of International Conference Proceedings, 2021)
The purpose of this study was to find out how much income and efficient value level of oranges in orange groves in TanjungBeringin village. Determination of the location of the study is done purposive sampling (direct pointing) with data collection saturated sampling technique is a sampling technique that makes all members of the population as samples. With the condition that the existing population is less than 30 people, because there are as many as 20 people. The method of data collection is done by interview. Data analysis techniques used to calculate income, cost and the level of efficiency value of citrus farming businesses using the R /C Ratio analysis tool. The results of the study showed the total cost, income, and profits of citrus farming business. The total cost of producing oranges is Rp1.600.000.000/year and an average of 80.000.000/members of the peasant group/ha/yr. Total orange income of Rp2.720.000.000/year with an average of Rp136.000.000/member of the farmer group/ha/yr. The value of R /C Ratio of citrus farming business of 2.7 is feasible to implement.